TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK INVESTASI BERBENTUK ARISAN (Studi Kasus pada Komunitas Yud’s Money Machine di Surabaya) - saiful sulum (Universitas Muhammadiyah Surabaya, 2019)
AbstrakField research was conducted at the Yud’s Money Machine community in Surabaya with the aim at answering how investment practices based on arisan systems are owned by the community of Yud’s Money Machine in Surabaya, as well as Islamic perspective regarding such investment practices.The method used in this study is a qualitative method, i.e. a research paradigm to describe events, phenomena, behavior of people or situations in a particular place in detail and in-depth in the form of narration. This type of research is field research. As for the approach used there, it is is a case study namely a qualitative approach that examines certain